Oxidized Phospholipids, Lipoprotein(a), Lipoprotein-Associated Phospholipase A2 Activity, and 10-Year Cardiovascular Outcomes: Prospective Results From the Bruneck Study - Kiechl, Stefan; Willeit, Johann; Mayr, Manuel; Viehweider, Brigitte; Oberhollenzer, Martin; Kronenberg, Florian; Wiedermann, Christian J.; Oberthaler, Sabine; Xu, Qingbo; Witztum, Joseph L.; Tsimikas, Sotirios (Arteriosclerosis, thrombosis, and vascular biology, 2007)
BACKGROUND—Oxidized phospholipids (OxPL) circulate on apolipoprotein B-100 particles (OxPL/apoB), and primarily on Lp(a) lipoprotein (a) [Lp(a)]. The relationship of OxPL/apoB levels to future cardiovascular events is not known. METHODS AND RESULTS—The Bruneck study is a prospective population-based survey of 40- to 79-year-old men and women recruited in 1990. Plasma levels of OxPL/apoB and lipoprotein (a) [Lp(a)] were measured in 765 subjects in 1995 and incident cardiovascular disease (CVD), defined as cardiovascular death, myocardial infarction, stroke, and transient ischemic attack, was assessed from 1995 to 2005. During the follow-up period, 82 subjects developed CVD. In multivariable analysis, which included traditional risk factors, high sensitivity C-reactive protein (hsCRP), and lipoprotein-associated phospholipase A2 (Lp-PLA2) activity, subjects in the highest tertile of OxPL/apoB had a significantly higher risk of cardiovascular events than those in the lowest tertile (hazard ratio[95% CI] 2.4[1.3 to 4.3], P=0.004). The strength of the association between OxPL/apoB and CVD risk was amplified with increasing Lp-PLA2 activity (P=0.018 for interaction). Moreover, OxPL/apoB levels predicted future cardiovascular events beyond the information provided by the Framingham Risk Score (FRS). The effects of OxPL/apoB and Lp(a) were not independent of each other but they were independent of all other measured risk factors. CONCLUSIONS—This study demonstrates that OxPL/apoB levels predict 10-year CVD event rates independently of traditional risk factors, hsCRP, and FRS. Increasing Lp-PLA2 activity further amplifies the risk of CVD mediated by OxPL/apoB.